2021
DOI: 10.1155/2021/5558304
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively Expressed Transcripts Analysis of Non-Small Cell Lung Cancer Cells under Different Hypoxic Microenvironment

Abstract: Globally, non-small cell lung cancer (NSCLC) is the most fatal form of malignancy. Numerous studies have shown that people living at high altitudes are at a higher risk for cancer. Hypoxia is one of the most important features in high altitude area. Compared with normal cells, cancer cells are more adapted to hypoxia atmosphere. However, at high altitudes, hypoxic conditions are also accompanied by other altered environmental conditions. To identify the single influence of hypoxia, we performed second-generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Our findings indicated that the risk score formula was associated with PFS and treatment responses in patients with NSCLC undergoing anti-PD-1/PD-L1 therapy. The IMvigor210 study examined the effect of PD-L1 inhibitor treatment in patients with metastatic urothelial cancer ( Mariathasan et al, 2018 ; Wang S. et al, 2021 ). Because relatively few patients were enrolled in the GSE135222 and GSE126044 cohorts, we further evaluated the formula in the IMvigor210 cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated that the risk score formula was associated with PFS and treatment responses in patients with NSCLC undergoing anti-PD-1/PD-L1 therapy. The IMvigor210 study examined the effect of PD-L1 inhibitor treatment in patients with metastatic urothelial cancer ( Mariathasan et al, 2018 ; Wang S. et al, 2021 ). Because relatively few patients were enrolled in the GSE135222 and GSE126044 cohorts, we further evaluated the formula in the IMvigor210 cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Another study proved that DDX49 participated in the promotion of the growth of NSCLC cells and lymph node metastasis via increasing the Akt/β-catenin pathway ( Lian et al, 2020 ). In NSCLC, KXD1 overexpression was positively correlated with cancer invasion and metastasis and negatively correlated with non-surgical anti-cancer treatment resistance ( Wang et al, 2021 ). NR2C2AP, which was highly expressed in NSCLC, also known as TRA16, could promote cancer cell growth by enhancing the ERβ signaling pathway and was associated with lymph node metastasis and poor OS ( Fang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…LUAD is a major type of lung cancer with a high incidence rate ( Li Z. et al, 2021 ; Wang et al, 2021 ). The prognosis of LUAD remains devastating because of its obscure pathogenesis ( Peng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%